Literature Review : The Effect Of Work Stress On The Risk Of Hypertension - Ika Alfina Sari.B; Imran Safei; Dzul Ikram (Sean Institute, 2025)
Hypertension is a leading cause of morbidity and mortality worldwide, with work-related stress identified as a significant risk factor. This study aims to explore the relationship between work stress and the risk of hypertension through a literature review (narrative review). Literature data were obtained from databases such as PubMed and Google Scholar, with inclusion criteria encompassing studies published in the last five years. The analysis results indicate that work stress can elevate blood pressure through the mechanism of stress hormone release, such as cortisol and adrenaline. Additionally, work-related factors such as high workload, long working hours, and unfavorable working environmental conditions contribute to an increased risk of hypertension. The research also indicates that workers experiencing work stress have a higher prevalence of hypertension compared to those who do not experience stress. Preventing hypertension in the workplace requires a holistic approach, including effective stress management, reduction of excessive working hours, and promotion of healthy lifestyles among workers. Company policy interventions and regulations related to occupational health are crucial for reducing the incidence of hypertension among workers. By understanding the relationship between work stress and hypertension, it is hoped that more effective preventive measures can be taken to enhance the health and well-being of workers.